Age Group Comparisons of TENS Response among Individuals with Chronic Axial Low Back Pain - Simon, Corey B. (J Pain, 2015)
Chronic low back pain (CLBP) is a highly prevalent and disabling musculoskeletal pain condition among older adults. Transcutaneous electrical nerve stimulation (TENS) is commonly used to treat CLBP, however, TENS response for older adults compared to younger adults is untested. In a dose-response study stratified by age, sixty participants with axial CLBP (20 young, 20 middle-aged, 20 older) received four 20-minute sessions of high frequency, high intensity TENS over a two to three-week period in a laboratory-controlled setting. Experimental measures of pain sensitivity (mechanical pressure pain detection threshold, PPT) and central pain excitability (phasic heat temporal summation, TS; heat aftersensations, AS) were assessed before and after TENS. Episodic or immediate axial CLBP relief was assessed after TENS via measures of resting pain, movement-evoked-pain, and self-reported disability. Cumulative or prolonged axial CLBP relief was assessed by comparing daily pain report across sessions. Independent of age, individuals experienced episodic increase in PPT and reduction in AS following TENS application. Similarly, all groups, on average, experienced episodic axial CLBP relief via improved resting pain, movement-evoked pain, and disability report. Under this design, no cumulative effect was observed as daily pain did not improve for any age group across the four sessions. However, older adults received higher TENS amplitude across all sessions in achieving similar TENS responses to younger adults. These findings suggest that older adults experience similar episodic axial CLBP relief as younger individuals following high frequency, high intensity TENS when higher dosage parameters are used.